Palatine tonsils functional reserve in children by immunological indicators evaluation - O. Bredun; I. Kosakivska; O. Melnikov (Group of Companies Med Expert, LLC, 2022)
Today, indications for tonsillectomy are based mainly on clinical criteria rather than on the functional state of palatine tonsils (PT). Determination of secretory immunoglobulin A (sIgA) levels in the oropharyngeal secretion before and after antigen load on PT is one of the methods for determining their functional capacity. However, this method has certain disadvantages, in particular not only PT were in the area of influence of both specific and non-specific stimuli, but also other lymphoid structures of the pharynx. The aim of the study is to improve the assessment of the immunofunctional state of PT. Materials and methods. The authors investigated by enzyme-linked immunosorbent assay (ELISA) sIgA and IFN-α content in oropharyngeal secretions in children with CT before and after antigen challenge vaccine OM-85 and the physical impact of ultrasound frequency of 880 kHz on the palatine tonsils. All the results were statistically processed using U-test (Mann-Whitney-Wilcoxon test) and Fisher's z-transformation. Results and Conclusion. The proposed method has significant advantages over the existing one, namely it is more selective, and therefore more accurate in determining the functional state of PT. Increased levels of sIgA and IFN-α in children's oropharyngeal secretions suggest maintaining the functional reserve of the tonsils; the absence of positive dynamics or negative dynamics of this indicator shows a functional failure of PT and can serve as an indication for surgical treatment of children with CT. The research was carried out in accordance with the principles of the Declaration of Helsinki. The research protocol was approved by the Local Ethics Committee of all the institutions mentioned in the work. Informed consent of the children's parents was obtained for the research. No conflict of interests was declared by the authors.